2018
DOI: 10.1002/ijc.31759
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific genome‐wide association study in glioblastoma identifies increased proportion of ‘lower grade glioma’‐like features associated with younger age

Abstract: Glioblastoma (GBM) is the most common malignant brain tumor in the United States. Incidence of GBM increases with age, and younger age-at-diagnosis is significantly associated with improved prognosis. While the relationship between candidate GBM risk SNPs and age-at-diagnosis has been explored, genome-wide association studies (GWAS) have not previously been stratified by age. Potential age-specific genetic effects were assessed in autosomal SNPs for GBM patients using data from four previous GWAS. Using age di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…The proneural GBM subtype is associated with improved prognosis [ 13 ], but is an uncommon entity in eGBM [ 14 ]. eGBM lack the isocitrate dehydrogenase ( IDH ) mutations [ 15 ] that confer survival advantage [ 16 , 17 ] and are rarely found in gliomas of older patients [ 17 19 ]. Only 3 of 126 gliomas of older patients in the Neurooncology Working Group (NOA) of the German Cancer Society Study 8 (NOA-08) [ 20 ] and 2 of 299 gliomas of older patients in the Nordic trials were found to have an IDH R132H mutation [ 21 ].…”
Section: Molecular Signature Of Gbm In Older Adultsmentioning
confidence: 99%
“…The proneural GBM subtype is associated with improved prognosis [ 13 ], but is an uncommon entity in eGBM [ 14 ]. eGBM lack the isocitrate dehydrogenase ( IDH ) mutations [ 15 ] that confer survival advantage [ 16 , 17 ] and are rarely found in gliomas of older patients [ 17 19 ]. Only 3 of 126 gliomas of older patients in the Neurooncology Working Group (NOA) of the German Cancer Society Study 8 (NOA-08) [ 20 ] and 2 of 299 gliomas of older patients in the Nordic trials were found to have an IDH R132H mutation [ 21 ].…”
Section: Molecular Signature Of Gbm In Older Adultsmentioning
confidence: 99%
“…Some other studies have also used diverse features to depict the common and different features for GBM and LGG. There was a higher prevalence of “LGG”‐like tumor characteristics in GBM samples in those patients that were 18–53 years old . Overall, we integrated comprehensive molecular characteristics to identify GBM‐ and LGG‐specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher prevalence of "LGG"-like tumor characteristics in GBM samples in those patients that were 18-53 years old. 43 Overall, we integrated comprehensive molecular characteristics to identify GBM-and LGG-specific genes. Our analysis provides novel insights that can be used to study the mechanisms of and treatment for GBM and LGG.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is poor with a median survival estimated at 16 months in clinical studies (28) and around 12 months in contemporary population-based studies (9). Approximately 5% of patients survive more than 5 years (10). Favorable therapy-independent prognostic factors include lower age and higher neurological performance status at diagnosis.…”
Section: Introductionmentioning
confidence: 99%